SKRINING PRENATAL ATTACHMENT TERHADAP RISIKO DEPRESI PADA IBU HAMIL DI WIKAYAH KERJA PUSKESMAS SUNGAI JINGAH: Prenatal Attachment Screening For The Risk Of Depression In Pregnant Women In The Working Area Of Sungai Jingah Public Health Center - Yuliantie, Putri; Mariana, Frani (LPPM - STIKES Pemkab Jombang, 2025)
Antenatal depression is a common mental health problem among pregnant women and can negatively impact both the mother and the fetus. One protective factor believed to reduce the risk of depression is prenatal attachment, the emotional bond between mother and fetus during pregnancy. At the Sungai Jingah Community Health Center, a study found that some pregnant women complained of anxiety, fatigue, difficulty sleeping, and excessive worry regarding the condition of the fetus and the delivery process. Ten respondents admitted to frequently feeling anxious and demotivated, having experienced sleep disturbances and prolonged feelings of sadness. This study aimed to determine the relationship between prenatal attachment and the risk of antenatal depression among pregnant women in the Sungai Jingah Community Health Center's work area. The study used a quantitative analytical design with a cross-sectional approach. A sample of 30 pregnant women was selected through purposive sampling. The instruments used were the Prenatal Attachment Inventory (PAI) to measure maternal attachment to the fetus and the Edinburgh Postnatal Depression Scale (EPDS) to measure the risk of depression. Data analysis was performed using the Chi-Square test. The results showed that the majority of respondents had a moderate prenatal attachment category (60%). The risk of antenatal depression was found to be 70% non-risk. Chi-square analysis showed a significant association between prenatal attachment and the risk of antenatal depression (p < 0.05). Prenatal attachment is associated with the risk of antenatal depression. Mothers with low prenatal attachment are at higher risk of depression during pregnancy. Interventions to improve prenatal attachment are needed during pregnancy to prevent antenatal depression.